Tourist revisit intention in post covid-19 pandemica modified perspective from Theory of planned behavior (TPB) - Hamdi Anugrah; Maruf (Enrichment : Journal of Management, 2023)
The Covid 19 pandemic that has occurred for almost the last three and give a bad impact on tourism industry, especially West Sumatra. The number of tourist visits sharply reduce due to the fearnes of various risks. In January 2023, Indonesian government officially revoked the PPKM (social distancing) regulations, it makes most activities returned to normal, including tourism activities. Seeing this opportunity, it is time to all parties to take the right actions and policies so that Indonesian tourism, especially West Sumatra, can revive. The purpose of this research is to examine the relationship between attitude, subjective norm and perceived behavioral control: a Modified perspective form theory of planned behavior on tourist revisit intention to visit Sirandah Island, West Sumatra, it is mediated by perceived risk variables. 165 respondents were taken as samples in this study using a non-probability sampling technique, and distributing questionnaires using an online application (google form) to tourists who had visited Sirandah Island. The results showed that the modified perspective of the theory of planned behavior (attitudes, subjective norms, and perceptions of behavioral control) has a significant effect on perceived risk. Furthermore, the perception of risk has a significant effect on the intention and attitude of tourists to return, subjective norms, perceptions of behavioral control have a significant effect on the intention to return. Attitudes, subjective norms, and perceptions of behavioral control have a direct effect on tourists' return visits through perceived risk as a mediating variable.